Exploratory research about the selective cleaning of calcium sulfate sediments on archaeological potteries. (25th April 2020) - Liu, Yan; Yang, Fuwei; Wang, Liqin
Abstract : A novel cleaning method for the selective removal of calcium sulfate sediments on archaeological potteries was studied. Abstract : A safe cleaning method was explored for the removal of calcium sulfate sediments on archaeological potteries. Using this method, calcium sulfate sediments were selectively removed and the potteries remained untouched. The cleaning effect was investigated via scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD), capillary water adsorption and color difference determination. The cleaning mechanism was also discussed. Due to its high selectivity, this method is safe and promising for clearing harmful calcium sulfate sediments on archaeological potteries.